Inflammation-Based Scores Predict Responses to PD-1 Inhibitor Treatment in Intrahepatic Cholangiocarcinoma - Yang Z; Zhang D; Zeng H; Fu Y; Hu Z; Pan Y; Chen J; Wang J; Zhang Y; Zhou Z; Xu L; Hu D; et al. (Dove Medical Press, 2022)
Zhenyun Yang,1,2,* Deyao Zhang,1,2,* Huilan Zeng,1,2,* Yizhen Fu,1,2 Zili Hu,1,2 Yangxun Pan,1,2 Jinbin Chen,1,2 Juncheng Wang,1,2 Yaojun Zhang,1,2 Zhongguo Zhou,1,2 Li Xu,1,2 Dandan Hu,1,2 Minshan Chen1,2 1State Key Laboratory of Oncology in South China, Sun Yat-Sen University Cancer Center, Collaborative Innovation Center for Cancer Medicine, Guangzhou, Guangdong, 510060, People’s Republic of China; 2Department of Liver Surgery, Sun Yat-Sen University Cancer Center, Guangzhou, Guangdong, 510060, People’s Republic of China*These authors contributed equally to this workCorrespondence: Dandan Hu; Minshan Chen, Tel +86-20-87343828 ; +86-20-87343117, Fax +86-20-87343585, Email hudd@sysucc.org.cn; chenmsh@sysucc.org.cnPurpose: Inflammatory response is related to tumor progression and patient survival. We aimed to clarify the prognostic value of the inflammation-based scores in intrahepatic cholangiocarcinoma (ICC) patients receiving anti-PD1 therapy.Patients and Methods: A total of 73 patients who received anti-PD-1 therapy from February 2019 to February 2021 were included in the study. Representative inflammation-based prognostic scores, including C-reactive protein (CRP), the platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-CRP ratio (LCR), lymphocyte-to-monocyte ratio (LMR), systemic immune inflammation index (SII), CRP-to-albumin ratio (CAR), prognostic nutritional index (PNI), Glasgow Prognostic Score (GPS), and prognostic index (PI), were assessed for prediction accuracy using Kaplan–Meier survival curves and time-dependent receiver operating characteristic (ROC). All the ten inflammation-based prognostic scores were measured before receiving anti-PD1 therapy.Results: All the ten inflammation-based prognostic scores showed good discriminatory ability in terms of overall survival (OS) (all P < 0.01), the higher the score, the worse the prognosis, while the CRP score was a remarkable independent predictor for OS in multivariate analysis (hazard ratio, 6.032; confidence interval, 2.467– 14.752; P < 0.001). The area under the ROC curve at 6 months, 12 months, 18 months and 24 months consistently demonstrated that the predictive value of the CRP score was superior to other inflammation-based scores.Conclusion: Inflammation-based scores predict the efficacy of anti-PD-1 therapy in patients with ICC and CRP score superior to the other inflammation-based prognostic scores in terms of predictive ability.Keywords: inflammation-based score, intrahepatic cholangiocarcinoma, anti-PD-1 treatment, overall survival, C-reactive protein